Susceptibility of Tetranychus ogmophallos (Acari: Tetranychidae) to Beauveria bassiana and Metarhizium anisopliae - Barbosa, Tarniris dos Santos [UNESP]; Andrade, Daniel Junior de [UNESP]; Polarzczyle, Ricardo Antonio [UNESP]; Duarte, Rogerio Teixeira (Florida Entomological Soc, 2018)
Tetranychus ogmophallos Ferreira & Flechtmann (Acari: Tetranychidae) is an emergent pest in peanut (Arachis hypogaea L. [Fabaceae]) and an important pest of forage peanut (A. pintoi Krapov. & W.C. Greg. [Fabaceae]). The susceptibility of T. ogmophallos to Beauveria bassiana (Balsamo) Vuillemin (Cordycipitaceae) and Metarhizium anisopliae (Metschnikof) Sorokin (Clavicipitaceae) was evaluated under laboratory and greenhouse conditions. In the laboratory, adult T. ogmophallos females were treated with B. bassiana and M. anisopliae using a Potter's tower, and in the greenhouse, bio-insecticides were applied on infested peanut plants. Both fungal suspensions containing 10(8) conidia per mL caused greater mortality in adult T. ogmophallos females. At 7 d after treatment under laboratory conditions, B. bassiana resulted in 100% mortality and M. anisopliae almost 100% mortality. Bio-insecticides substantially reduced the mite population density under greenhouse conditions when applied to infested peanut plants, with mite populations reduced 84% and 92% by B. bassiana and M. anisopliae, respectively. Under greenhouse conditions, the increase in the number of mites per plant observed at 15 d after treatment suggests the need to repeat the entomopathogen application. Our results demonstrate that B. bassiana and M. anisopliae are promising biological agents to control T. ogmophallos. The practical application of this work for managing T. ogmophallos population on peanut crop is discussed.
Keywords: peanut red mite; Arachis hypogaea; Arachis pintoi; microbial control; forage peanut